Excess maternal salt intake produces sex-specific hypertension in offspring: putative roles for kidney and gastrointestinal sodium handling. - Gray, Clint; Al-Dujaili, Emad A.; Sparrow, Alexander J.; Gardiner, Sheila M.; Craigon, Jim; Welham, Simon J.M.; Gardner, David S. (Public Library of Science, 2013)
Hypertension is common and contributes, via cardiovascular disease, towards a large proportion of adult deaths in the Western World. High salt intake leads to high blood pressure, even when occurring prior to birth - a mechanism purported to reside in altered kidney development and later function. Using a combination of in vitro and in vivo approaches we tested whether increased maternal salt intake influences fetal kidney development to render the adult individual more susceptible to salt retention and hypertension. We found that salt-loaded pregnant rat dams were hypernatraemic at day 20 gestation (147±5 vs. 128±5 mmoles/L). Increased extracellular salt impeded murine kidney development in vitro, but had little effect in vivo. Kidneys of the adult offspring had few structural or functional abnormalities, but male and female offspring were hypernatraemic (166±4 vs. 149±2 mmoles/L), with a marked increase in plasma corticosterone (e.g. male offspring; 11.9 [9.3-14.8] vs. 2.8 [2.0-8.3] nmol/L median [IQR]). Furthermore, adult male, but not female, offspring had higher mean arterial blood pressure (effect size, +16 [9-21] mm Hg; mean [95% C.I.]. With no clear indication that the kidneys of salt-exposed offspring retained more sodium per se, we conducted a preliminary investigation of their gastrointestinal electrolyte handling and found increased expression of proximal colon solute carrier family 9 (sodium/hydrogen exchanger), member 3 (SLC9A3) together with altered faecal characteristics and electrolyte handling, relative to control offspring. On the basis of these data we suggest that excess salt exposure, via maternal diet, at a vulnerable period of brain and gut development in the rat neonate lays the foundation for sustained increases in blood pressure later in life. Hence, our evidence further supports the argument that excess dietary salt should be avoided per se, particularly in the range of foods consumed by physiologically immature young.